Effect of Cultured and Natural Thallus, and Symbionts Extracts of Usnea articulata on Skin Wound Healing in Wistar Rat - T Valadbeigi; S Rashki (Institue of Medicinal Plants, ACECR, 2014)
Background: Lichens are one of the appropriate biological models for biotechnological studies that produce a great variety of secondary metabolites by use of in vitro cultures. Various biological activities of these components are known, such as: anti-viral, anti-bacterial, anti-tumor, anti-inflammatory, and anti-protozoal. Objective: In the present research, the purpose is the study of the effect of natural and cultured thalli and symbionts (alga and fungus in separate) extracts of Usnea articulata on skin wound healing in vivo conditions. Methodes: The collected samples were washed and dried in the shade. Thallus and lichen symbionts (after isolation) were cultured separately. Thin-layer chromatography for the natural and cultured thallus and the symbionts were done. Than methanolic extract of thalli and symbionts were prepared and their effects on wound healing were investigated. Results: Methanolic extract of natural thalli had only usnic acid, tissus cultute had usnic acid and 2 unknown components. Symbionts had no usnic acid. Methanolic extract of natural thalli and that callus were effective in the process of wound healing. They showed a meamingful difference with other groups under treatment. While metanolic extract of mycobiont and phycobiont callus did not have any effect on wound healing process. Conclusion: obviously, the formation of usnic acid is based on phisyological relationship between phycobiont and mycobiont. So they are not observed in the seprate symbionts.